The Digital Revolution in Chronic Pain Management: AI, mHealth, and the Future of Personalized Care - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Chronic pain, defined as persistent or recurrent pain lasting longer than three months, represents a significant global health challenge, affecting an estima...
Keywords: Drug Discovery; Digital Health; Artificial Intelligence; Healthcare Innovation; Wearable Technology